Markov Chain Model And Performance Enhancement For EDCA Protocol - Abu-Khadrah, Ahmed Ismail Mohammad; Zakaria, Zahriladha; Othman, Mohd Azlishah; Mohd Zin, Mohd Shahril Izuan (Journal Of Communications, 2016)
-